Danzig. Der Dominikanerplatz C. A. Mann. - Mann, Conrad Anton (18..-18..) (Lith. Inst v. C.G. Kanter in Marienwerder, 1855)
Przedstawia Plac Dominikański w Gdańsku od północy, widziany z Podwala Staromiejskiego.